Designing a Classroom Marking Scheme to Assess Translation Quality: An Implementation of House’s Translation Quality Assessment Analysis - Alvin Taufik (Journal of English Language and Culture, 2020)
The goal of this research is to design a marking scheme to aid on the assessment translation quality. The research will start with the analysis on the element of the text which will be the focus of the assessment as determined by House (2001). The elements which will be analyzed are taken from both Source Language (SL) and Target Language (TL). The data gathered will then be compared. The comparison is aimed to determine the most influential factors in the rendering of texts. Afterwards, the factors will be put together in a scheme and graded or marked in accordance to the needs of the assessment in the classroom. The expected result will hopefully be able to be used by professionals and amateurs assessors.